A high barrier polymer film for yogurt packaging and preparation method thereof

By modified polyethylene glycol (PVA) and put it on the PLBI film to form a high-resistance polymer (PLBI/PVA-G-AC) film, solving the existing yogurt packaging materials The problem of corruption realizes higher oxygen and ultraviolet blocking performance, and extend the shelf life of yogurt.

CN118515879BActive Publication Date: 2025-01-28INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410710209.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-01-28
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

During storage and transportation, existing yogurt packaging materials are susceptible to microorganisms, temperature, oxygen and light radiation, resulting in the decline in the quality of yogurt or spoilage. The white pollution caused by traditional plastics is severe, so it is necessary to develop a highly degradable high-barrier packaging material. .

Method used

By accurately control the amount of acryllisyl chlorine, the polyvinyl (PVA) is modified to prepare a polyethylene-G-acryl chloride (PVA-G-AC) with ultraviolet lighting performance, and the assistance Below, through the water-soluble UV solidification reaction, the modified PVA-G-AC is single-sided on the PLBI film to form a high-resistance polymer (PLBI/PVA-G-AC) film.

Benefits of technology

It significantly improves the oxygen blocking performance, ultraviolet barrier performance and mechanical performance of the thin film, extend the shelf life of yogurt, slows the changes in acidity and the decline in protein content, and improves the storage effect of yogurt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515879B_ABST
    Figure CN118515879B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of polymer materials, and in particular to a high-barrier polymer film that can be used for yogurt packaging and a preparation method thereof. The present application first modifies polyvinyl alcohol to obtain a polyvinyl alcohol-g-acryloyl chloride polymer with ultraviolet light curing performance. After a water-soluble UV curing reaction, polyvinyl alcohol-g-acryloyl chloride is grafted on one side of the poly (L-lactic acid-co-butylene itaconate) film to form a new type of high-barrier polymer film. The high-barrier polymer film has the environmentally friendly characteristics of biodegradability, and after modification, its elongation at break has been significantly improved, and the oxygen and ultraviolet light blocking properties have also been greatly improved. The present application has important application prospects in many fields, especially in the field of yogurt packaging. The high-barrier polymer film can effectively isolate the adverse effects of the external environment on the quality and flavor of yogurt, and significantly extend the shelf life of yogurt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a high-barrier polymer film that can be used for yogurt packaging and a preparation method thereof. Background Art

[0002] In today's market, white pollution caused by traditional plastics is serious. Various countries have also promulgated relevant policies, prompting the packaging industry to move towards biodegradable development.

[0003] Polylactic acid is one of the most promising biodegradable materials that can replace petroleum-based plastics. Polylactic acid is composed of lactic acid units, which are divided into L-type and D-type. Poly (L-lactic acid) (PLLA) is a biocompatible and biodegradable aliphatic bio-based polyester with excellent physical properties, biocompatibility, bioabsorbability, durability and transparency, suitable for short-term or disposable food packaging. Polyvinyl alcohol (PVA) is a commonly used electrospinning material, which is non-toxic, biocompatible and widely used in the medical field. The U.S. Food and Drug Administration (FDA) has allowed it to be used as oral tablets and topical preparations. PVA has good barrier properties to N2, O2, CO2 and water vapor and is biodegradable.

[0004] PLLA and PVA have good synergistic properties. PLLA has good mechanical properties and biocompatibility, but poor barrier properties, while PVA has high barrier properties and good chemical stability. The Chinese patent document with patent number CN101235155A discloses that PLLA and PVA are blended to prepare nano- and micro-fiber membranes, and their degradation properties can be controlled. However, this method still cannot avoid the problem of poor compatibility of the two materials.

[0005] In addition, studies have shown that unsaturated aliphatic polyester with side double bonds, namely poly (butylene itaconate) (PBI), is obtained by esterification and polycondensation of unsaturated itaconic acid and 1,4-butanediol under certain conditions. Introducing poly (butylene itaconate) (PBI) into the main chain of PLLA to obtain poly (L-lactic acid-co-butylene itaconate) (PLBI) can promote cross-linking between chain segments and improve mechanical properties. However, there are few reports on how to modify PLLA or PLBI to further improve its gas barrier, UV barrier and other properties.

[0006] During the packaging, storage and transportation of yogurt, it is easy to be affected by microorganisms, temperature, oxygen and light radiation, which may lead to quality degradation or even spoilage. Therefore, the packaging material should have a certain barrier property to prevent spoilage caused by microorganisms or oxygen. At present, the storage technology of yogurt is increasingly concerned, and the selection of packaging materials is an important link to ensure the flavor and nutritional quality of yogurt. Therefore, the research of a degradable packaging with high barrier properties is the key point of current research. Summary of the invention

[0007] In view of this, the present application proposes an innovative modification method, which precisely controls the amount of acryloyl chloride (AC) added to modify polyvinyl alcohol (PVA) to prepare polyvinyl alcohol-g-acryloyl chloride (PVA-g-AC) with UV curing properties. Then, with the assistance of a photoinitiator, the modified PVA-g-AC is grafted onto a PLBI film on one side through a water-soluble UV curing reaction, thereby forming a new type of high barrier polymer (PLBI / PVA-g-AC) film.

[0008] Compared with PLBI film, this modified high barrier polymer film has achieved significant improvements in multiple key properties. It not only shows a higher elongation at break, but also has excellent oxygen barrier properties and UV barrier properties.

[0009] Especially in the field of yogurt packaging, the application effect of the new high-barrier polymer film is particularly significant. Compared with PLBI film, the high-barrier polymer film of the present application shows better performance in gas barrier and water retention. Therefore, when the film is used to package yogurt, it can effectively slow down the change in the acidity of yogurt, reduce the decrease in protein content, and reduce the decrease in the activity of lactic acid bacteria, thereby significantly extending the shelf life of yogurt and improving the storage effect of the product.

[0010] The technical solution of this application is achieved as follows:

[0011] In a first aspect, the present application provides a high barrier polymer, comprising the following structural formula:

[0012]

[0013] In the formula, (m+n+y) / (m+n+y+l)=alcoholysis degree; y:(x+y):(x+y+z)=(1-5):8:100; m, n, l, x, y, z are all positive integers.

[0014] The alcoholysis degree is the alcoholysis degree of polyvinyl alcohol in the reaction raw material of the high barrier polymer.

[0015] In a second aspect, the present application provides a method for preparing a high barrier polymer film, comprising the following steps:

[0016] S1. Add polyvinyl alcohol particles into deionized water, stir until the solution is clear and transparent, then drop acryloyl chloride, react at 22-25° C. for 12-18 hours to obtain a polyvinyl alcohol-g-acryloyl chloride solution;

[0017] S2, prepare a mixed solution of photoinitiator solution, distilled water, polyvinyl alcohol-g-acryloyl chloride solution and methanol solution, pour the mixed solution into a liquid paved with poly (L-lactic acid-co-butylene itaconate)

[0018] The bottom plate of the film is irradiated with ultraviolet light for 15 to 30 seconds, and the high barrier polymer film is obtained after drying.

[0019] In a third aspect, the present application provides an application of the high-barrier polymer or a high-barrier polymer film prepared by the preparation method described in any one of the above items, wherein the application includes at least one of the following uses: (1) blocking oxygen; (2) blocking ultraviolet rays; (3) packaging and storage of food, beverages, cosmetics or medicines. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 FTIR spectra of PLBI, PVA, PVA-g-AC and PLBI / PVA-g-AC films (wavelength range 4000~700cm -1 );

[0022] Figure 2 FTIR spectra of PLBI, PVA, PVA-g-AC and PLBI / PVA-g-AC films (wavelength range 2000~1000cm -1 );

[0023] Figure 3 Scanning electron micrographs of PLBI and PLBI / PVA-g-AC films, where A corresponds to PLBI film, and BF correspond to PLBI / PVA-g-AC1 to 5 films, respectively;

[0024] Figure 4 The results of the determination of the titratable acidity of the yogurt during storage in Comparative Example 1 and Application Examples 1 to 5 are as follows;

[0025] Figure 5 The results of measuring the water holding capacity of the yogurt during storage of Comparative Example 1 and Application Examples 1 to 5 are as follows;

[0026] Figure 6 The results of protein determination during storage of yogurt in Comparative Example 1 and Application Examples 1 to 5 are as follows;

[0027] Figure 7 The results are shown in Table 1, which are the results of measuring the number of lactic acid bacteria during storage of yogurt in Comparative Example 1 and Application Examples 1 to 5. DETAILED DESCRIPTION

[0028] The relevant terms and their abbreviations in this application are shown in Table 1:

[0029] Table 1 Terms and abbreviations

[0030] abbreviation the term I A Itaconic acid BDO 1,4-Butanediol AC Acryloyl chloride PLLA Poly (L-lactic acid) OLLA Oligo(L-lactic acid) PBI Polybutylene itaconate PLBI Poly (L-lactic acid-co-butylene itaconate) PVA-g-AC Polyvinyl alcohol-g-acryloyl chloride PVA Polyvinyl acetate

[0031] The high barrier polymer film described in the present application can be written as PLBI / PVA-g-AC composite film or PLBI / PVA-g-AC film, which have the same meaning and can be replaced with each other.

[0032] PLLA and PVA have good synergistic properties, but the synthesis reaction of PLLA and PVA has problems such as strict reaction conditions and difficult synthesis. In previous studies, the method of blending the two is usually adopted, but this method still cannot avoid the problem of poor compatibility of the two materials. In view of this, the present application modifies PVA on the basis of the PLBI film made of modified PLLA, so that the synthesis conditions of PLLA and PVA are simple and efficient, thereby preparing a polymer material with excellent performance.

[0033] The synthesis process of the high barrier polymer (PLBI / PVA-g-AC) involves the following principles:

[0034] The high barrier polymer (PLBI / PVA-g-AC) is a grafting reaction product of PLBI and PVA-g-AC. PVA-g-AC is grafted onto the surface of the PLBI film on one side through an ultraviolet curing reaction.

[0035] Among them, the chemical structure of PVA-g-AC is shown as follows:

[0036]

[0037] In the formula, b:(a+b+c)=(1-20):100, (a+b) / (a+b+c)=alcoholysis degree, and a, b, and c are all positive integers.

[0038] The synthetic reaction principle of PVA-g-AC mainly involves graft copolymerization, in which acryloyl chloride reacts with the PVA main chain as a grafting monomer, that is, acryloyl chloride reacts with the hydroxyl group (-OH) on the PVA main chain as a grafting monomer. The acyl chloride group of acryloyl chloride reacts with the hydroxyl group on the PVA main chain to form an ester bond (-COO-), thereby grafting acryloyl chloride onto the PVA main chain. The product obtained after the grafting reaction is a PVA-g-AC copolymer.

[0039] In addition, PVA is made from polyvinyl acetate (PVAc) through alcoholysis. During the alcoholysis process, the acetoxy group (-OCOCH3) in PVAc is replaced by a hydroxyl group (-OH) to form PVA. The alcoholysis degree indicates the degree to which the acetoxy group in the polymer chain is replaced by a hydroxyl group, that is, the content of hydroxyl groups in the polymer chain (i.e. a+b).

[0040] The chemical structure of PLBI is shown below:

[0041]

[0042] Wherein, d:(d+e)=8:100, d and e are both positive integers.

[0043] PLBI is also a PLBI copolymer, specifically a high molecular weight poly(L-lactic acid-co-butylene itaconate) copolymer.

[0044] The reaction principle of the synthesis process of PLBI includes: copolymerizing OLLA and PBI to form a copolymer composed of two structural units of OLLA and PBI (as shown in the above formula).

[0045] Among them, the structural unit of PBI is -O-CO-CH(=CH2)-CO-O-(CH2)4-O-; therefore, the PLBI copolymer not only retains the biocompatibility and degradability of poly (L-lactic acid), but also improves its mechanical properties by introducing unsaturated biopolyester PBI, and on the other hand, introduces new reaction sites into poly (L-lactic acid), so that poly (L-lactic acid) can be introduced with other groups or polymer segments, thereby realizing functional modification.

[0046] Finally, through a water-soluble ultraviolet curing reaction, the double bonds of PVA-g-AC and PLBI are opened respectively, and new double bonds are formed, and PVA-g-AC is single-sidedly grafted onto the surface of the PLBI film to obtain the PLBI / PVA-g-AC composite film.

[0047] To this end, the embodiments of the present application disclose at least the following technical solutions:

[0048] In a first aspect, the present application provides a high barrier polymer, comprising the following structural formula:

[0049]

[0050] In the formula, (m+n+y) / (m+n+y+l)=alcoholysis degree; y:(x+y):(x+y+z)=(1-5):8:100; m, n, l, x, y, z are all positive integers.

[0051] In a second aspect, the present application provides a method for preparing a high barrier polymer film, comprising the following steps:

[0052] S1. Add polyvinyl alcohol particles into deionized water, stir until the solution is clear and transparent, then drop acryloyl chloride, react at 22-25° C. for 12-18 hours to obtain a polyvinyl alcohol-g-acryloyl chloride solution;

[0053] S2, prepare a mixed solution of photoinitiator solution, distilled water, polyvinyl alcohol-g-acryloyl chloride solution and methanol solution, pour the mixed solution into a liquid paved with poly (L-lactic acid-co-butylene itaconate)

[0054] The bottom plate of the film is irradiated with ultraviolet light for 15 to 30 seconds, and the high barrier polymer film is obtained after drying.

[0055] In some preferred embodiments, in step S1, the molar ratio of polyvinyl alcohol to acryloyl chloride is 1:(0.5-1.5), and more preferably 1:1.25.

[0056] In some preferred embodiments, in step S2, in the mixed solution, the volume ratio of the photoinitiator solution, distilled water, polyvinyl alcohol-g-acryloyl chloride solution and methanol solution is (1-5):50:(35-45):9, and more preferably 1:50:40:9.

[0057] In some preferred embodiments, in step S2, the photoinitiator solution includes at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0058] In some preferred embodiments, the mass fraction of the photoinitiator solution is 98%, and the mass fraction of the methanol solution is 99.5%.

[0059] In some preferred embodiments, in step S2, the wavelength of the ultraviolet light irradiation is 240-400 nm.

[0060] In some preferred embodiments, the preparation method of the poly (L-lactic acid-co-butylene itaconate) film comprises the following steps: firstly, oligo (L-lactic acid) and poly (butylene itaconate) are subjected to a grafting reaction in a mass ratio of 92:8, and the obtained graft copolymer product is dissolved in chloroform, and then cast into a mold and cured to form the poly (L-lactic acid-co-butylene itaconate) film.

[0061] In some preferred embodiments, the molecular weight of the oligo(L-lactic acid) is 2000-5000 Da.

[0062] In a third aspect, the present application provides an application of the high-barrier polymer or a high-barrier polymer film prepared by the preparation method described in any one of the above items, wherein the application includes at least one of the following uses: (1) blocking oxygen; (2) blocking ultraviolet rays; (3) packaging and storage of food, beverages, cosmetics or medicines.

[0063] In order to make the purpose, technical scheme and advantages of the present application clearer, the present application is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. The reagents not described separately in detail in the present application are all conventional reagents and can be obtained from commercial channels; the methods not described in detail are all conventional experimental methods and can be obtained from the prior art.

[0064] The main sources of raw materials in the examples of this application are as follows:

[0065] L-lactic acid, purity ≥90.0%, purchased from Aladdin Biochemical Technology Co., Ltd.; polyvinyl alcohol (PVA), alcoholysis degree 88-99% (mol / mol); acryloyl chloride, purchased from Aladdin Biochemical Technology Co., Ltd.; 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMMP), purchased from Beijing Solebow Technology Co., Ltd.; itaconic acid (IA) and 1,4-butanediol (BDO), purity ≥99.0%, purchased from Sigma-Aldrich, USA; chloroform (CHCl3) and anhydrous ethanol were purchased from Sinopharm Reagent Company.

[0066] Example 1

[0067] In this embodiment, PLLA is first modified, and PBI is introduced into the PLLA main chain through a melt polycondensation reaction to obtain PLBI; secondly, PVA is modified with acryloyl chloride to obtain a PVA-g-AC polymer, and then a water-soluble UV curing reaction is used to graft PVA-g-AC onto the PLBI film. The specific steps are as follows:

[0068] 1.1 Preparation of PLBI film

[0069] First, itaconic acid and 1,4-butanediol were weighed and mixed in a three-necked flask at a molar ratio of 1:1, sealed, and placed in an oil bath. The reaction device was replaced with argon three times, and reacted at 150°C for 2 hours under argon protection. The vacuum was continued for 4 hours to finally obtain a clear yellow liquid, namely PBI.

[0070] 700g of L-lactic acid (L-LA) was weighed and poured into a 2L reactor equipped with a stirrer and a condensation reflux device, and placed in an oil bath heating device. Nitrogen was purged 3 times, first dehydrated at 110°C and 40kPa for 1h, then heated to 150°C and adjusted to 13kPa for 2h, and finally heated to 180°C and adjusted to 4kPa, and vacuumed for 4h. The above operation was used to fully distill the water in L-lactic acid by gradient decompression to obtain oligomeric lactic acid (OLLA, molecular weight range of 2000-5000Da).

[0071] PBI was added to OLLA in a mass ratio of (8:92), and catalysts SnCl2·2H2O and TSA were added. The amount of catalyst added was 0.5% of the total reactant mass. The reaction was vacuumed at 180°C for 20 hours until the viscosity of the reactant increased to the point where the stirrer could not rotate. The reactant was cooled at room temperature to obtain a crude product that was crushed into powder. Finally, 5g of PLBI was weighed and dissolved in 80ml of chloroform, mixed thoroughly, and cast into a mold. After the chloroform evaporated, the film was removed from the mold and dried in a vacuum drying oven.

[0072] 1.2 Preparation of modified PVA

[0073] Weigh 2.2 g of polyvinyl alcohol (PVA) particles into a conical flask, and measure 100 ml of deionized water and stir thoroughly on a magnetic stirrer until the solution becomes clear and transparent. PVA and acryloyl chloride (AC) are added dropwise in a molar ratio of 1:0.5, respectively, and react at room temperature for 12 h to obtain a PVA-g-AC solution.

[0074] 1.3 Preparation of PLBI / PVA-g-AC composite membrane

[0075] 1% (V / V) photoinitiator (HMMP), 50% (V / V) distilled water, 40% (V / V) PVA-g-AC solution, and 9% (V / V) methanol were fully mixed, 50 ml was measured and poured evenly on a glass plate covered with PLBI film, and after UV (360nm) irradiation for 15s, it was fully eluted with deionized water and placed in a vacuum drying oven for use. PLBI was single-sidedly grafted with PVA-g-AC, and the resulting reaction product was named PLBI / PVA-g-AC1.

[0076] Example 2

[0077] The difference between this embodiment and embodiment 1 is that the molar ratio of PVA to acryloyl chloride (AC) in step 1.2 is changed from 1:0.5 to 1:0.75, respectively. The remaining steps are the same, and the obtained reaction product is named PLBI / PVA-g-AC2.

[0078] Example 3

[0079] The difference between this embodiment and embodiment 1 is that the molar ratio of PVA to acryloyl chloride (AC) in step 1.2 is changed from 1:0.5 to 1:1, and the remaining steps are the same. The obtained reaction product is named PLBI / PVA-g-AC3.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that the molar ratio of PVA to acryloyl chloride (AC) in step 1.2 is changed from 1:0.5 to 1:1.25, respectively. The remaining steps are the same, and the obtained reaction product is named PLBI / PVA-g-AC4.

[0082] Example 5

[0083] The difference between this embodiment and embodiment 1 is that the molar ratio of PVA to acryloyl chloride (AC) in step 1.2 is changed from 1:0.5 to 1:1.5, respectively. The remaining steps are the same, and the obtained reaction product is named PLBI / PVA-g-AC5.

[0084] (I) The following performance tests were performed on the PLBI / PVA-g-AC composite films prepared in Examples 1 to 5:

[0085] 2.1 Infrared spectrum test

[0086] PVA, PVA-g-AC, PLBI, and PLBI / PVA-g-AC films were measured by infrared with a resolution of 4 cm -1 , wavelength range 400~4000cm -1 , scanned 64 times.

[0087] 2.2 Mechanical properties test

[0088] Tensile strength and elongation at break were measured using a tensile testing machine (XLW (EC), Jinan Languang Electromechanical Technology Co., Ltd., China). According to ASTM D882-09, the film thickness was about 90 μm, and the samples were cut into 28 mm × 5 mm rectangular strips and tested on the testing machine at a speed of 10 mm / min. Each group had 10 parallels and the average value was taken.

[0089] 2.3 Oxygen barrier performance test

[0090] Oxygen permeability was measured by a gas permeability tester (VAC-V2, Jinan Languang Electromechanical Technology Co., Ltd., China) according to GB / T1038-2000. The test thickness was 90 μm and the test environment conditions were (temperature: 23° C., relative humidity: 50%).

[0091] 2.4 Scanning electron microscope test

[0092] Field emission scanning electron microscopy (FESEM) (Apreo S LoVac, Thermo Fisher, USA) was used for observation. The test acceleration voltage was 5 kV. In order to increase conductivity, all samples were plated with a 10 nm thick Au layer before observation.

[0093] 2.5 UV blocking performance test

[0094] The transmittance of the PLBI / PVA-g-AC composite film in the range of 200-800 nm was tested using an ultraviolet-visible-near infrared spectrophotometer (UV-Vis, Cary 5000). The average transmittance of the film in the ultraviolet range was calculated according to formula (1).

[0095]

[0096] Where: is the average transmittance of the film, is the transmittance at the corresponding wavelength, and is the number of points in the wavelength range of 280 to 400 nm.

[0097] (II) The performance test results are as follows:

[0098] 3.1. Infrared spectrum test results

[0099] Depend on Figure 1 It can be seen that the PVA film has a wavelength of 1650 cm -1 The curve at 3400cm- -1 The small peak near the membrane is caused by the -OH contained in PVA. After the PVA grafted with acryloyl chloride is fully eluted, the peak at 1657 cm -1 A new peak appears at 1720, 1246, and 1030 cm -1 The peak intensities at all locations are enhanced, which are small peaks caused by unsaturated or saturated ester bonds, further proving the success of PVA modification.

[0100] Figure 2 It can be seen that the PLBI film has a wavelength of 1650 cm -1 There is a relatively gentle -C=C- peak at 1650cm-1 After the PLBI / PVA-g-AC film was fully eluted, the wavelength at 1650 cm -1 The double bond peak intensity at 1670 cm -1 A new peak appears at , that is, the carbon-carbon double bond peak blue-shifts. It may be that PLBI and PVA-g-AC will open their double bonds respectively during the water-soluble UV curing process to form new double bonds (the yellow part in the figure), which further proves that PVA-g-AC is successfully grafted onto the surface of the PLBI film.

[0101] 3.2 Scanning electron microscopy results

[0102] like Figure 3 As shown in Figure 3, the surface of the PLBI film is flat and smooth. Some small particles were observed on the surface of the PLBI / PVA-g-AC composite film, and as the molar ratio of PLBI grafted to PVA-g-AC increased, the film surface became rough and the particles on the film became dense, indicating that PVA-g-AC was successfully grafted to the PLBI film.

[0103] 3.3 Mechanical properties test

[0104] As shown in Table 2, the tensile strength of PLBI is 8.6 MPa and the elongation at break is 181.7%. The tensile strengths of Examples 1 to 5 are 6.9, 7.4, 7.3, 7.1, and 7.5 MPa, respectively. Although the tensile strengths have decreased, the changes are not significant. The elongations at break of the PLBI / PVA-g-AC composite films are 189.4%, 200.4%, 236.8%, 239.7%, and 275.8%, respectively, but the elongations at break have increased compared to PLBI. This further proves that the PLBI / PVA-g-AC composite film provided in this application improves the toughness of the film.

[0105] Table 2 Tensile properties of PLBI / PVA-g-AC composite films of Examples 1-5

[0106]

[0107] 3.4 Oxygen barrier performance test results

[0108] The lower the gas permeability of the film material, the stronger the gas barrier performance. The oxygen barrier performance of PLBI and PLBI / PVA-g-AC films at 23°C is shown in Table 3. The O2 permeability of PLBI film is 48.33 cm 3 ·m 2 ·d -1After the surface of the PLBI film was grafted with PVA-g-AC, the O2 permeation rate decreased by 40 to 50 times. With the increase of the molar ratio of grafted PVA-g-AC, the O2 permeation rate of the film showed a trend of first decreasing and then increasing. The oxygen permeation rates of the PLBI / PVA-g-AC films obtained in Examples 1 to 5 at 23°C were 3.40, 2.67, 1.74, 1.47, and 2.87 cm 3 / (m 2 ·d). The increase in oxygen barrier performance of PLBI / PVA-g-AC film may be due to the good oxygen barrier performance of PVA itself. Therefore, within a certain range, as the molar ratio of modified PLLA grafted PVA-g-AC increases, the oxygen barrier performance of PLBI / PVA-g-AC film improves. The oxygen permeability of PLBI / PVA-g-AC4 film at 23°C is 1.47 cm 3 / (m 2 ·d), oxygen permeability is 1.38×10 -8 cm 3 m / (m 2 ·d·Pa), its oxygen barrier performance is the best.

[0109] Table 3 Oxygen permeability of PLBI and PLBI / PVA-g-AC composite films

[0110]

[0111] 3.5 UV blocking performance test results

[0112] Typically, packaging materials are measured for both UV transmittance and visible light transmittance.

[0113] 200-400nm belongs to the ultraviolet band. As shown in Table 4, compared with PLBI, the average ultraviolet transmittance of PLBI / PVA-g-AC film shows a trend of first increasing and then decreasing with the increase of the molar ratio of grafted PVA-g-AC, which are 41.1%, 15.3%, 11.1%, 12.3%, 10.1%, and 17.0%, respectively. The PLBI / PVA-g-AC4 film has the lowest average ultraviolet transmittance of 10.1%, and has the best ultraviolet shielding performance.

[0114] 400-760nm belongs to the visible light band, and the transmittance at 600nm is usually used as an indicator of the transparency of film materials. The transmittance of PLBI film at 600nm is 85.2%; with the increase of the molar ratio of grafted PVA-g-AC, the transmittance of PLBI / PVA-g-AC film presents a "U"-shaped growth curve, and the transmittance of PLBI / PVA-g-AC4 film is the lowest at 55.8% at 600nm, with the best visible light blocking performance.

[0115] Table 4 UV blocking properties of PLBI and PLBI / PVA-g-AC composite films

[0116]

[0117]

[0118] (III) Application of the PLBI / PVA-g-AC film of the present application in yogurt packaging

[0119] In the application examples, comparative example 1 (group) uses PLBI film as yogurt packaging; application example 1 (group) uses PLBI / PVA-g-AC1 film as yogurt packaging; application example 2 (group) uses PLBI / PVA-g-AC2 film as yogurt packaging; application example 3 (group) uses PLBI / PVA-g-AC3 film as yogurt packaging; application example 4 (group) uses PLBI / PVA-g-AC4 film as yogurt packaging; application example 5 (group) uses PLBI / PVA-g-AC5 film as yogurt packaging. Yogurt storage quality index tests were performed according to the following methods:

[0120] 1) Titratable acidity

[0121] Refer to the method in GB 5413.34-2010 "National Food Safety Standard for Determination of Acidity of Milk and Dairy Products", use the titration acidity method, expressed in degrees Gilner (°T). Pour 10g of yogurt and 20mL of distilled water into a conical flask, shake it thoroughly, add two drops of phenolphthalein reagent, and titrate with a 0.1% NaOH solution. Stop the titration when a light pink color appears and does not fade within 30 seconds. Multiply the number of milliliters of NaOH consumed by 10 to get the total acidity. Perform three parallel determinations and take the average value.

[0122] 2) Water holding capacity

[0123] Weigh and record the mass of the centrifuge tube, put in about 10g of yogurt and weigh its total mass, centrifuge at 5000r / min for 10min, discard the supernatant, weigh the remaining mass, and use the formula:

[0124] Water holding capacity / % = centrifugal sediment weight / sample weight × 100%

[0125] Three groups of parallel measurements were performed and the average value was taken.

[0126] 3) Protein determination

[0127] According to the method of GB5009.5-2016 "Determination of Protein in Food", 10g of yogurt was weighed into a digestive tube, and then 6g of potassium sulfate and 0.4g of copper sulfate were added, followed by 30mL of sulfuric acid solution, and the mixture was placed in a graphite digester for digestion and waited for the mixture to cool to room temperature. The digested reagent was titrated with a Kjeldahl nitrogen analyzer (K9860) to obtain the result.

[0128] 4) Number of viable lactic acid bacteria

[0129] The total lactic acid bacteria count method was used for determination according to GB 4789.35-2016 "Food Microbiology Test for Lactic Acid Bacteria". The total lactic acid bacteria count was determined every 5 days during storage, and MRS medium was selected as the plate count for lactic acid bacteria. 10 -5 , 10 -6 , 10 -7 Dilution gradient, 3 parallels for each gradient, counting according to national standards.

[0130] The test results of yogurt storage quality indicators are as follows:

[0131] 1) Titratable acidity

[0132] Acidity is an important indicator for evaluating the freshness and sensory properties of yogurt. During the storage of yogurt, the acidity of yogurt increases due to the influence of lactic acid bacteria. Using PLBI and PLBI / PVA-g-AC as packaging materials, the titratable acidity of yogurts with different materials during storage was tested. Figure 4 Among them, the titratable acidity of PLBI changed the most, and the group grafted with PVA-g-AC changed the least. This is because the oxygen barrier property of yogurt packaging can determine the oxygen content of yogurt packaging, and Lactobacillus bulgaricus and Streptococcus thermophilus used in fermenting yogurt are both facultative anaerobic bacteria. The micro-oxygen environment will accelerate the post-acidification of yogurt, resulting in poor yogurt quality and flavor. PLBI / PVA-g-AC4 exhibits good gas barrier properties, its acidity changes less, and its storage effect is better.

[0133] 2) Water holding capacity

[0134] Water holding capacity is an important indicator for evaluating yogurt quality. As a gel system, yogurt has a network structure that can hold small molecules such as water. The internal network structure is mainly composed of protein, which gives yogurt an excellent taste and maintains the stability of the yogurt structure. As the acidification progresses during storage, the internal network structure of the yogurt is destroyed, the stored water molecules will flow out, and the quality of the yogurt will decline. Therefore, water holding capacity can reflect the quality of yogurt. Figure 5It shows that the water holding capacity of all packaged yogurts has a similar trend, but the water holding capacity of the yogurt in the comparative example 1 (PLBI) group decreases the fastest, from 93% to 80.3% on the 20th day, while the yogurt in the application examples 1 to 5 groups still maintains good water holding performance on the 20th day, which are 84.3%, 84%, 86.3%, 88% and 85.7% respectively. Studies have shown that the water holding capacity of yogurt is related to the lactic acid bacteria in the yogurt. During the post-acidification process of yogurt, lactic acid bacteria grow and multiply, the protein in the yogurt is used by microorganisms, the gel system formed by the protein is destroyed, and the water combined with the gel is released, resulting in whey separation. In addition, at the same protein content, the ratio of casein to whey protein will also affect the water holding capacity of yogurt. In general, the water holding capacity of the yogurt packaged in the application examples is higher than that of the comparative example group, among which the application example 4 is the best.

[0135] 3) Protein determination

[0136] Yogurt is a dairy product rich in fat, protein and other nutrients, and is very popular among people. Protein plays an important role in human health, and the protein content can well reflect the quality changes of yogurt. Figure 6 As shown in the figure, after 20 days of yogurt storage, the protein content of the control group decreased to 2.83%, while the application examples decreased to 2.94%, 3.02%, 3.12%, 3.15% and 3.02%, respectively. Among them, application example 4 showed a higher protein level. The main reason for showing this structure is attributed to the high barrier property of the film of application example 4. The high barrier property of the film inhibits the decomposition and consumption of protein by lactic acid bacteria in yogurt. According to the national standard GB 19302-2010, the five groups of application examples in this experiment all meet the national standard (protein content ≥ 2.9%).

[0137] 4) Number of viable lactic acid bacteria

[0138] The number of lactic acid bacteria in yogurt is also an important indicator for evaluating the quality of yogurt. The lactic acid bacteria in yogurt have probiotic properties and can effectively improve the gastrointestinal function of the human body and regulate intestinal flora. Figure 7 The results show that the number of lactic acid bacteria in the control group decreased the most, while the change in application example 4 was the smallest. The number of lactic acid bacteria in yogurt is affected by the oxygen content and ultraviolet light in the yogurt. In the later stage of storage, the lactic acid produced by the metabolism of lactic acid bacteria accumulates, and the growth of lactic acid bacteria is inhibited. Ultraviolet light also affects the growth of lactic acid bacteria. Application Example 4 delays the post-acidification of yogurt due to its excellent gas barrier and light barrier properties, so the yogurt quality is better.

[0139] The above description is only a preferred implementation mode of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a high barrier polymer film, characterized in that: The steps include: S1. Add polyvinyl alcohol particles into deionized water, stir until the solution is clear and transparent, then drop acryloyl chloride, react at 22-25° C. for 12-18 hours to obtain a polyvinyl alcohol-g-acryloyl chloride solution; S2, preparing a mixed solution of a photoinitiator solution, distilled water, polyvinyl alcohol-g-acryloyl chloride solution and a methanol solution, pouring the mixed solution into a bottom plate covered with a poly (L-lactic acid-co-butylene itaconate) film, irradiating with ultraviolet light for 15 to 30 seconds, and obtaining the high barrier polymer film after drying; In the step S1, the molar ratio of polyvinyl alcohol to acryloyl chloride is 1:(0.5-1.5); In the step S2, in the mixed solution, the volume ratio of the photoinitiator solution, distilled water, polyvinyl alcohol-g-acryloyl chloride solution and methanol solution is (1-5):50:(35-45):9; The preparation method of the poly (L-lactic acid-co-butylene itaconate) film comprises the following steps: Firstly, oligo(L-lactic acid) and poly(butylene itaconate) are subjected to melt polycondensation reaction in a mass ratio of 92:8, and the obtained graft copolymer product is dissolved in chloroform, cast in a mold, and solidified to form the poly(L-lactic acid-co-butylene itaconate) film; The molecular weight of the oligo(L-lactic acid) is 2000-5000Da.

2. The method for preparing a high barrier polymer film according to claim 1, characterized in that: In the step S2, the photoinitiator solution includes at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

3. The method for preparing a high barrier polymer film according to claim 2, characterized in that: In the step S2, the mass fraction of the photoinitiator solution is 98%, and the mass fraction of the methanol solution is 99.5%.

4. The method for preparing a high barrier polymer film according to claim 2, characterized in that: In the step S2, the wavelength of the ultraviolet light irradiation is 240-400 nm.

5. Use of the high barrier polymer film prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The application includes at least one of the following uses: (1) blocking oxygen; (2) blocking ultraviolet rays; (3) packaging and storage of food, beverages, cosmetics or medicines.

Citation Information

Patent Citations

  • Method for preparing polylactic acid, polyvinyl alcohol and brazilwood mixed nano or micron fibrous membrane

    CN101235155A

  • Degradable polymer film and production method thereof

    CN109294190A

  • Polyvinyl alcohol modified polylactic acid film, and preparation method and application thereof

    CN111647257A